2013
DOI: 10.1074/jbc.m113.472563
|View full text |Cite
|
Sign up to set email alerts
|

The Antiparasitic Clioquinol Induces Apoptosis in Leukemia and Myeloma Cells by Inhibiting Histone Deacetylase Activity

Abstract: Background: Clioquinol is a potent chelator of divalent metal ions including zinc. Results: Clioquinol fits the zinc-centered active pocket of HDACs and inhibits HDAC activity, which results in cell cycle arrest and cancer cell apoptosis. Conclusion: Clioquinol inhibits HDAC activity and induces blood cancer cell death. Significance: This is the first report to demonstrate that clioquinol inhibits HDAC activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 50 publications
2
36
0
Order By: Relevance
“…For example, the HDAC inhibitor SAHA was found to induce autophagic cell death24. Our recent study demonstrated that clioquinol can also inhibit HDACs10, but whether clioquinol-induced autophagy is due to its action as an inhibitor of proteasomes or as an inhibitor of HDAC is not clear yet, the present study showed that clioquinol induces both apoptosis and autophagy. Moreover, its action on apoptosis can be partly abrogated by 3-MA, a major inhibitor of autophagy.…”
Section: Discussionsupporting
confidence: 44%
“…For example, the HDAC inhibitor SAHA was found to induce autophagic cell death24. Our recent study demonstrated that clioquinol can also inhibit HDACs10, but whether clioquinol-induced autophagy is due to its action as an inhibitor of proteasomes or as an inhibitor of HDAC is not clear yet, the present study showed that clioquinol induces both apoptosis and autophagy. Moreover, its action on apoptosis can be partly abrogated by 3-MA, a major inhibitor of autophagy.…”
Section: Discussionsupporting
confidence: 44%
“…In addition to the effects on histone transcription factors, a lot of HDAC inhibitors are known that they can affect non-histone transcription factors including p53 and tubulin [35,36]. In thyroid cancers, HDAC inhibitors sodium butyrate and trichostatin A have been reported to inhibit the growth of anaplastic thyroid cancer cells due to the promotion of apoptosis and the induction of cell cycle arrest, both of which are independent of p53 status [37].…”
Section: Discussionmentioning
confidence: 99%
“…Current studies have demonstrated that proteasomal inhibitors can modulate gene transcription in addition to modulating protein stability. Proteasomal inhibitors such as bortezomib and clioquinol have been demonstrated to regulate gene transcription by inhibiting histone deacetylases, thus regulating gene expression in an epigenetic manner (22,23).…”
Section: Discussionmentioning
confidence: 99%